Optimization of Distillation Conditions for Improved Recovery of Phthalides from Celery (Apium graveolens L.) Seeds - Adam Kokotkiewicz; Anna Badura; Żaneta Tabaczyńska; Andżelika Lorenc; Adam Buciński; Maria Luczkiewicz (Polish Journal of Food and Nutrition Sciences)
The essential oil of celery ( Apium graveolens ) is characterized by exceptionally high content of alkylphthalides. The mentioned compounds exhibit a number of biological effects (including hypotensive, lipid-lowering, neuroprotective, and cytotoxic) and are also responsible for distinctive aroma of the plant. In the current work, parameters of conventional hydrodistillation (HD) and simultaneous distillation-extraction (SDE) were optimized to obtain phthalide-enriched fractions of celery seeds. A positive correlation was shown between hydrodistillation time and improved essential oil and phthalide yields. The 6-h HD of comminuted seeds yielded essential oil (2.9%) with a higher total phthalide content (51%), as compared to the samples collected after 1.5-3.0 h, which gave 2.4-2.7% of oil containing 24.6-39.2% of total phthalides. The oil contained sedanenolide (36.7%), 3- n -butylphthalide (13.1%), and sedanolide (1.1%). A further increase in the total phthalide content was achieved by omitting the size reduction step prior to hydrodistillation (68.8%) and utilization of the salting-out effect (84.3%). Enzyme pretreatment had a negligible effect on essential oil and phthalide yields. The change of distillation mode from HD to SDE significantly increased the oil yield of whole seeds (from 2.8 to 5.8% for 6 h processing) while maintaining its high phthalide content (62.5%), which translated to an increase in the total phthalide yield from 19.4 to 36.0 g/kg.